IMPACT OF MARKETING CAMPAIGNS ON SALES DYNAMICS (CADDY, MULTIVAN) - Hrysiuk, Tetiana (Global Prosperity, 2025)
The modern automotive market is under the influence of digital transformations, the growing role of behavioral analytics and growing competition in the passenger and commercial vehicle segment. In a dynamic market, the study of the effectiveness of marketing campaigns accompanying the release of new models, in particular the Volkswagen Caddy and Multivan, is of particular relevance. Such campaigns not only shape demand, but also determine the trajectory of market activity in the short and medium term. The problem lies in the insufficient number of applied studies that would analyze the impact of marketing activities on the actual dynamics of sales from the standpoint of measured KPIs. To determine the impact of marketing campaigns on changes in sales volumes of Volkswagen Caddy and Multivan models in Ukraine, with the identification of key indicators of the effectiveness of communication strategies. The study confirmed the growth of sales of both models after marketing launches: Caddy - over 40%, Multivan - up to 35% in the first three months. The most effective tools were video reviews, targeted digital campaigns, localized content and partnership activities with auto experts. A list of KPIs was determined to assess the effectiveness of such campaigns: change in sales volumes, number of media contacts, growth in search activity, coverage of video materials. In further research, it is advisable to focus on building an integrated KPI system taking into account behavioral factors and analyzing the effectiveness of individual digital channels to predict market reaction to new products.